2003
DOI: 10.1097/01.prs.0000046034.02158.eb
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the Volume of Vascularized Tissue Formation in Engineered Constructs: An Experimental Study in Rats

Abstract: The authors have previously described a model of in vivo tissue generation based on an implanted, microsurgically created vessel loop in a plastic chamber (volume, 0.45 ml) containing a poly(DL-lactic-co-glycolic acid) (PLGA) scaffold. Tissue grew spontaneously in association with an intense angiogenic sprouting from the loop and almost filled the chamber, resulting in a mean amount of tissue in chambers of 0.23 g with no added matrix scaffold and 0.33 g of tissue in PLGA-filled chambers after 4 weeks of incub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(47 citation statements)
references
References 25 publications
0
47
0
Order By: Relevance
“…In this study we were able to demonstrate the feasibility of using VEGF and bFGF immobilized in a fibrin-based drug delivery system in the AVL model in the rat. This model was first described by Erol and Spira 1979 (21) and enhanced by Morrison et al, who inserted the AVL into polycarbonate isolation chambers (6,22). Lokmic et al showed that the AVL without any matrix is able to produce a highly vascularized construct (29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study we were able to demonstrate the feasibility of using VEGF and bFGF immobilized in a fibrin-based drug delivery system in the AVL model in the rat. This model was first described by Erol and Spira 1979 (21) and enhanced by Morrison et al, who inserted the AVL into polycarbonate isolation chambers (6,22). Lokmic et al showed that the AVL without any matrix is able to produce a highly vascularized construct (29).…”
Section: Discussionmentioning
confidence: 99%
“…In (6,22). This concept allows vascularization and subsequent transfer of biomaterials independent of local conditions at the recipient site.…”
Section: Introductionmentioning
confidence: 99%
“…Morrison and co-workers augmented this model and implanted the AV-loop into polycarbonate isolation chambers. Furthermore they induced vascularization in polymer matrices and managed to generate large volumes of axially vascularized tissue [133][134][135]. In the era of tissue engineering this concept met with great interest.…”
Section: "Free-style" Vascularized Bioartificial Bone Graftsmentioning
confidence: 99%
“…9 In 2011, the initial 5 mL of adipose flap successfully expanded to 56.5 mL using large volume chamber (78.5 mL) in pig model, providing clinically relevant volumes of tissue for soft tissue construction. 10 Despite the advancement of tissue engineering chamber technique in recent years, [11][12][13] the final maximum volume of the flap was still unable to fill the chamber thoroughly for unknown reasons.…”
mentioning
confidence: 99%